Pemberantasan Perdagangan Orang Dengan Sarana Hukum Pidana - Erdianto Effendi (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2013)
Combating Human Trafficking Through Criminal Law. In modern day slavery does not exist anymore. However, the practice of slavery in modern times transforms into human trafficking. Trafficking in persons in general can be defined as a condition where people, especially women and children, are for sale to work and they are forced to be involve in prostitution. Then the question is, how is it necessary to criminalize human trafficking? This article concludes that the actions to criminalize human trafficking is right based on the theory of crime. In addition, it is in line with the politics of state law as reflected in the national long-term development plan. DOI: 10.15408/jch.v1i1.2982